A preliminary study of the effects of glucosamine sulphate and chondroitin sulphate on surgically treated and untreated focal cartilage damage - Kamarul, Tunku; Abdul Rahim, S.; Tumin, M.; Selvaratnam, L.; Ahmad, T.S. (AO Research Institute Davos, 2011)
The effects of Glucosamine Sulphate (GS) and Chondroitin Sulphate (CS) on the healing of damaged and repaired articular cartilage were investigated. This study was conducted using 18 New Zealand white rabbits as experimental models. Focal cartilage defects, surgically created in the medial femoral condyle, were either treated by means of autologous chondrocyte implantation (ACI) or left untreated as controls. Rabbits were then divided into groups which received either GS+/-CS or no pharmacotherapy. Three rabbits from each group were sacrificed at 12 and 24 weeks post-surgery. Knees dissected from rabbits were then evaluated using gross quantification of repair tissue, glycosaminoglycan (GAG) assays, immunoassays and histological assessments. It was observed that, in contrast to untreated sites, surfaces of the ACI-repaired sites appeared smooth and continuous with the surrounding native cartilage. Histological examination demonstrated a typical hyaline cartilage structure; with proteoglycans, type II collagen and GAGs being highly expressed in repair areas. The improved regeneration of these repair sites was also noted to be significant over time (6 months vs. 3 months) and in GS and GS+CS groups compared to the untreated (without pharmacotherapy) group. Combination of ACI and pharmacotherapy (with glucosamine sulphate alone/ or with chondroitin sulphate) may prove beneficial for healing of damaged cartilage, particularly in relation to focal cartilage defects.